EFEKTIVITAS FUNGSI KANTOR URUSAN AGAMA SEBAGAI NADZIR PENGELOLAAN HARTA WAKAF - Cecep Moch Ramli Al-Fauzi; faisal Faisal (Prodi Hukum Ekonomi Syariah (Muamalah), 2018)
Waqf is a treasure given by someone to take the benefits for the public interest, especially for the welfare of Muslims. The practice of waqf and representation in the community has not been fully orderly and efficient so that in many cases many waqf property which has been neglected and not properly maintained has even been transferred to third parties by way of violating the law. This happened because of the inability of nadzir in managing and developing waqf property in addition to the lack of public understanding of the function and role of waqf property. Representation that is carried out in the Office of Religious Affairs, starting from filling out the waqf form, endowment waqf pledge and giving a letter of introduction to make a certificate of membership in accordance with the Law of the Republic of Indonesia Number 41 of 2004 concerning Waqf and recorded in detail by the KUA to be recorded. KUA as a government agency that is in direct contact with the community, one of its tasks is to play a role in the management of waqf property so that the results are effective according to existing procedures and clear designation.